Catalytic co-hydrothermal carbonization of food waste digestate and yard waste for energy application and nutrient recovery. (January 2022) - He, Mingjing; Zhu, Xiefei; Dutta, Shanta; Khanal, Samir Kumar; Lee, Keat Teong; Masek, Ondrej; Tsang, Daniel C.W.
Graphical abstract: Highlights: Non-catalytic co-HTC of FWD and YW marginally increased energy potential of hydrochar. Co-HTC with 0.5 M HCl exhibited the highest carbon utilization efficiency. Co-HTC with citric acid provided ∼3-fold increase in pressure with ∼74% C loss. Catalytic system of 0.5 M HCl had better overall energy and nutrient recovery performance. Ash content and mineral constituents were the decisive factors for combustion behaviour. Abstract: Hydrothermal carbonization (HTC) provides a promising alternative to valorize food waste digestate (FWD) and avoid disposal issues. Although hydrochar derived from FWD alone had a low calorific content (HHV of 13.9 MJ kg −1 ), catalytic co-HTC of FWD with wet lignocellulosic biomass ( e.g., wet yard waste; YW) and 0.5 M HCl exhibited overall superior attributes in terms of energy recovery (22.7 MJ kg −1 ), stable and comprehensive combustion behaviour, potential nutrient recovery from process water (2-fold higher N retention and 129-fold higher P extraction), and a high C utilization efficiency (only 2.4% C loss). In contrast, co-HTC with citric acid provided ∼3-fold higher autogenous pressure, resulting in a superior energy content of 25.0 MJ kg −1, but the high C loss (∼74%) compromised the overall environmental benefits. The results of this study established a foundation to fully utilize FWD and YW hydrochar for bioenergy application and resource recovery from the process water.